Quantitative MRI Evaluation of Tunnel placement in ACL Reconstruction. Issue 5 (31st May 2017) - Parker, David A.; Grasso, Samuel; Scholes, Corey; Fritsch, Brett; Li, Qing
Introduction: Positioning of the graft ACL in the native footprint center is important to replicate the anatomy and function of the ACL for each individual patient. It is known that incorrect bone tunnel placement for the reconstructed ligament is a contributor to poor clinical outcomes postoperatively. Currently the success of tunnel placement is determined by training and experience of the treating surgeon and there is no universally accepted quantifiable and objective method to evaluate the execution of these decisions. The goal of this project was to develop a quantitative routine assessment to assist pre-surgical planning and also evaluate the execution of femoral and tibial bone tunnel placement in ACL reconstructed knees. Methods: The study recruited failed primary ACL reconstructed patients (N=25) who consented to undergo revision ACL reconstruction to establish the placement of the graft ACL tunnel apertures in the femur and tibia. Prior to surgery each participant underwent high resolution 3 T MRI of their injured knee and 3D models were generated through segmentation of soft and hard tissue knee structures. During surgery previous graft tunnels and prominent reference landmarks visible on MRI and arthroscopically were registered using intraoperative navigation to act as the reference standard. The placement of the tunnel apertures in the femur and tibia were measured in all three planes using a novel measurement method. Results: Preliminary result show that the measurement method can assess the placement of tunnel apertures in the femur and tibia within 0.1 – 1.0 mm of the intraoperative data, using reference landmarks identifiable in MRI and arthroscopically. Additionally, the area of the tunnel aperture, bone tunnel volume can be evaluated. Reliability and validation of the novel method is ongoing using medical imaging and intraoperative navigation to register the placement of bone tunnels in revision ACL reconstruction patients. Conclusions: Correct placement of graft ACL bone tunnels inside the native ACL footprint is critical to the outcome of ACL reconstruction. Development of an accurate reproducible method for assessment of tunnel placement relative to the anatomical footprint should provide a simple method for objectively assessing ACL reconstructions. Preliminary results of this routine assessment suggests that graft tunnel placement can be objectively assessed to assist clinicians to evaluate and improve ACL reconstruction technique and evaluation of ACL reconstruction outcomes.